UK national cohort of anal cancer treated with intensity-modulated radiotherapy: One-year oncological and patient-reported outcomes. (March 2020) - Gilbert, A.; Drinkwater, K.; McParland, L.; Adams, R.; Glynne-Jones, R.; Harrison, M.; Hawkins, M.A.; Sebag-Montefiore, D.; Gilbert, D.C.; Muirhead, R.
Abstract: Background: Concurrent chemoradiotherapy is the standard treatment for anal cancer. Following national UK implementation of intensity-modulated radiotherapy (IMRT), this prospective, national cohort evaluates the one-year oncological outcomes and patient-reported toxicity outcomes (PRO) after treatment. Materials and methods: A national cohort of UK cancer centers implementing IMRT was carried out between February to July 2015. Cancer centers provided data on oncological outcomes, including survival, and disease and colostomy status at one-year. EORTC-QLQ core (C30) and colorectal (CR29) questionnaires were completed at baseline and one-year followup. The PRO scores at baseline and one year were compared. Results: 40 UK Cancer Centers returned data with a total of 187 patients included in the analysis. 92% received mitomycin with 5-fluorouracil or capecitabine. One-year overall survival was 94%; 84% were disease-free and 86% colostomy-free at one-year followup. At one year, PRO results found significant improvements in buttock pain, blood and mucus in stools, pain, constipation, appetite loss, and health anxiety compared to baseline. No significant deteriorations were reported in diarrhea, bowel frequency, and flatulence. Urinary symptom scores were low at one year. Moderate impotence symptoms at baseline remained at one year, and a moderate deterioration in dyspareunia reported. Conclusions: With national anal cancer IMRT implementation, at this early pre-defined time point, one-year oncological outcomes were reassuring and resulted in good disease-related symptom control. one-year symptomatic complications following CRT for anal cancer using IMRT techniques appear to be relatively mild. These PRO results provide a basis to benchmark future studies. Highlights: Significant improvements in pain, blood in stool and health anxiety at one-year. No significant deterioration in bowel or urinary symptoms. Moderate male and female sexual dysfunction reported. 94% one-year overall survival in a national cohort following anal cancer (chemo)IMRT.